Multivariate Analysis Revealed the Morphological Variability Among Crataegus Species - Ferhad MURADOĞLU; Saime GÜRSOY; Emrah GÜLER (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
The Crataegus genus has many species growing as wild that have positive effects on human health. The information about the phenotypic diversity of this species is rather inadequate. Phenotypic diversity among forty-four genotypes belonging to four Crataegus species (C. monogyna, C. orientalis, C. astrosanguinea, and C. meyeri) was determined based on morphological and physicochemical characteristics. Significant differences were observed among the species in terms of studied characteristics. Fruit weight ranges from 1.60 to 2.50 g for C. orientalis, 1.53 to 2.33 g for C. meyeri, 1.26 to 2.41 g for C. astrosanguinea, and 0.38 to 1.98 g for C. monogyna. The highest fruit length (15.19 mm) and width (17.58 mm) were determined in C. orientalis. The heights color values, L*, a*, and hueo values were highest in C. meyeri, while b* value was highest in C. monogyna and Chroma* was in C. orientalis. The highest TSS and pH were found in C. monogyna as 3.99% and 4.33%, respectively. TA was highest in C. monogyna with 1.83 mg L-1. Seed size ranged from 1.36 (C. monogyna) to 4.33 (C. orientalis), while seed weight ranged from 0.23 g to 0.45 g in C. mongyna and C. astrosanguinea, respectively. The correlation analysis indicated significant correlations between morphological characters. The principal component and clustering analyses revealed high phenotypic variety among and within the species, showing that the studied characters were useful for describing Crataegus species. The results provided valuable insights for morphological and colorimetric characterization of hawthorn species and their utilization.